2021
DOI: 10.1007/s10343-021-00572-4
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklungen des Insektizid-Einsatzes in Winterraps (Brassica napus L.) infolge des Anwendungsverbotes neonicotinoider Beizen

Abstract: ZusammenfassungDer Anbau von Winterraps (Brassica napus L.) wird durch das Auftreten tierischer Schaderreger begleitet, wodurch ein intensiver Insektizid-Einsatz nötig ist. Insbesondere das Anwendungsverbot neonicotinoider Beizen in Winterraps schränkt jedoch die Möglichkeiten der Insektenbekämpfung für landwirtschaftliche Betriebe in der Europäischen Union (EU) ein. Die vorliegende Studie untersucht den Insektizid-Einsatz landwirtschaftlicher Praxisbetriebe, um die Auswirkungen des Anwendungsverbotes neonicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…60 The taxing of plant protection products (according to ecotoxicity) would be another option to reduce pesticide use. [50][51][52][53][54][55][56][57][58][59][60][61][62] This can increase the cost of insecticide use and the positive economic effect of reducing insecticides. Moreover, the price advantage of certain active ingredients resulting from the tax may encourage their widespread use and exacerbate resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…60 The taxing of plant protection products (according to ecotoxicity) would be another option to reduce pesticide use. [50][51][52][53][54][55][56][57][58][59][60][61][62] This can increase the cost of insecticide use and the positive economic effect of reducing insecticides. Moreover, the price advantage of certain active ingredients resulting from the tax may encourage their widespread use and exacerbate resistance.…”
Section: Discussionmentioning
confidence: 99%
“…No data on the time taken for combined monitoring of weeds, diseases, and pests was collected, although such an approach would likely reduce the overall labor costs of plant protection as insect pests and fungal diseases can often be simultaneously detected, and the time spent monitoring single pests, insects, and weeds can therefore be reduced 39,40,55 . A study in 2021 in Mecklenburg‐Western Pomerania (Germany) showed that the applications of insecticides in OSR on farms during autumn quadrupled following the ban of neonicotinoid seed treatment in December 2013, 56 but this development did not occur on farms in North Rhine‐Westphalia during the trial period. These are probably regional and annual effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation